Bile Reflux Gastritis Patient Profile in DR. Saiful Anwar Malang Hospital - Nurisa, Fadhila; Supriono, Supriono (UI Scholars Hub, 2019)
Introduction. Bile reflux gastritis is bile reflux to gaster with fullness sensation, uncomfort, nausea, and vomiting. Bile reflux gastritis usually happens after surgery, as partial gastrectomy, truncal vagotomy, pyloroplasty, cholecystectomy, or sphinchteroplasty. This study aimed to determine the description of endoscopic of patients with bile reflux gastritis and the location of abnormalities found in endoscopy patient at Saiful Anwar Hospital Malang. Methods. Data were taken from the medical record of endoscopy patient in Saiful Anwar Hospital Malang from 2012 January the 1st until 2016 December the 31st that fulfill bile reflux gastritis inclusion criteria. Abnormality location divided near and far from pyloric. The location that near from pyloric is antrum, pyloric, duodenum, and distal duodenum. The location that far from pyloric is esophagus, esophagogastric-junction, fundus, corpus, and angulus. Results. Among 3,491 endoscopic patients, there were 1,949 gastritis patients (55.83%). A total of 1,949 gastritis patient, 124 fulfill bile reflux gastritis criteria. Four exclusion criteria (incomplete data), 120 patients bile reflux gastritis, 62 men (51.67%) and 58 women (48.33%). Hyperemia mostly at antrum (96), erosion mostly at antrum (43), edema mostly at pyloric (18), ulcer mostly at antrum (14). Presentation of hyperemia, erosion and edema far from pyloric as many as near the pyloric. More ulcer found near the pyloric (75.68%). Conclusions. Hyperemia, erosion, and ulcer mostly found at antum, edema mostly found at pyloric. Hyperemia, erosion, and edema spread in all of the parts. More ulcer found near the pyloric.